Strategi Pelestarian Seni Wayang melalui Atraksi Pertunjukan Berbasis Analisis SWOT di Museum Kota Tua Jakarta - Syifa Eliana Ahmad; Dyah Mustika Wardani; Gilang Fahreza (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Wayang is one of Indonesia's cultural heritages that has been recognized by UNESCO as an Intangible Cultural Heritage of Humanity and possesses significant historical, philosophical, and educational values. However, globalization, technological advancements, and changing public interests, particularly among the younger generation, have become major challenges to the preservation of wayang art. The Wayang Museum in Kota Tua Jakarta plays an important role in preserving this traditional art through wayang performances, collection exhibitions, educational activities, and various cultural programs aimed at increasing public appreciation of Indonesia's cultural heritage. This study aims to analyze the strategy for preserving wayang art through performance attractions at the Wayang Museum in Kota Tua Jakarta using a SWOT analysis. The research employed a descriptive method with a qualitative approach. Data were collected through observation, interviews, documentation, and literature review, and were analyzed using SWOT analysis to identify the internal and external factors influencing the preservation of wayang art. The results indicate that the Wayang Museum possesses several strengths, including its extensive wayang collection, regularly performances, and strategic location as a cultural tourism destination. On the other hand, the museum still faces several weaknesses, such as limited digital promotion and the low level of interest among the younger generation in wayang art.